Emission Reductions Program for Addressing Drivers of Deforestation and Forest Degradation: An Insight from the Terai Arc Landscape in Southern Nepal - Adhikari, S.; Baral, H. (Springer, 2022)
As part of the REDD+ program, for the past decade, Nepal has been working with the World Bank’s Forest Carbon Partnership Facility on its Emission Reductions Program (ER-Program). The ER-Program was designed for a program area covering 13 districts in the Terai Arc Landscape. Approved in 2018, the Emission Reductions Program Document (ERPD) identified six major drivers of deforestation and forest degradation in the program area: unsustainable and illegal harvesting of timber and fuelwood; overgrazing; forest fires; encroachment and conversion of forest land for other land uses; resettlement; and infrastructure development. The ER-Program aims to address these drivers and help the conservation and enhancement of existing forest carbon stock through the sustainable management of forest resources. To do so, seven program interventions have been designed, ranging from localized and improved community-based forest management, through private sector engagement in the forestry sector and alternative energy promotion, to integrated land-use planning. The February 2021 Emission Reductions Payment Agreement (ERPA) between the Government of Nepal and the World Bank has paved the way for official implementation of these interventions on the ground. These interventions unlock the potentiality of up to USD 45 million in results-based payments for emission reductions of up to nine million tons of carbon dioxide equivalent by 2025. Accordingly, the ER-Program is expected to address the drivers of emissions-causing deforestation and forest degradation and enhance forest carbon stock, ultimately paving the way for results-based payments for future emissions reductions.